The effects of the COVID-19 pandemic on the lives and social daily life of married individuals during the total curfew in Kuwait - Hend Al-Ma'seb; Maha Al-Sejari; David Kondrat (Journal of Affective Disorders Reports, 2023)
Background: Economic problems, social distancing, and drastic alterations to daily lifestyle behaviors during the COVID-19 pandemic affected individuals’ social relations worldwide. Objective: This cross-sectional study aimed to examine the impact of the COVID-19 pandemic on participants’ social relationships, diets, incomes, health, religious beliefs, and mental health. Method: An online questionnaire composed of demographic questions; questions regarding participants’ social, economic, and health lives; and two scales that measure depression, anxiety, stress and positive and negative suicide ideation inventory was distributed to 528 married couples. Results: The findings of this study showed significant differences between the independent variables and the dependent variables, which were the DASS and the PANSI. Conclusion: The findings from this study highlight the importance of beliefs about COVID-19 for the welfare of families. Furthermore, the findings contribute to the literature by examining how people's views of the effects of COVID-19 on social relations, healthy diets, incomes, health, and religion relate to mental health.